2020
DOI: 10.1088/1757-899x/713/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curing Conditions on Properties of Lightweight Concrete Brick Containing Expanded Polystyrene and Palm Oil Fuel Ash

Abstract: This study presents the effect of curing conditions towards properties of lightweight concrete brick made up of cement, sand and some replacement materials. The replacement materials used in this study is Expanded Polystyrene (EPS) as sand replacement and Palm Oil Fuel Ash (POFA) as cement replacement. The percentage of replacement for POFA is 0%, 10% and 20% whilst 0%, 30% and 50% for EPS. The brick samples have been exposed to different types of curing conditions that is air curing and water curing until the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…The continuous of C-S-H gel within a pore structure contribute to strength development in concrete [14]. Results achieved in recent study show an increase in compressive strength as curing age increased due to the formation of C-S-H gel [18]. In line with this current study; development of additional C-S-H gel was observed when clay brick waste was used in mortar and concrete in an experimental study [19].…”
Section: Unconfined Compressive Strength (Ucs)supporting
confidence: 85%
“…The continuous of C-S-H gel within a pore structure contribute to strength development in concrete [14]. Results achieved in recent study show an increase in compressive strength as curing age increased due to the formation of C-S-H gel [18]. In line with this current study; development of additional C-S-H gel was observed when clay brick waste was used in mortar and concrete in an experimental study [19].…”
Section: Unconfined Compressive Strength (Ucs)supporting
confidence: 85%